Description and Analysis of a Novel Subtype of the Anti-Synthetase Syndrome Characterized by Frequent Attacks of Fever and Systemic Inflammation in a Single-Center Cohort Study - Sun, Shuhui; Chen, Zhiwei; Zhang, Danting; Xu, Wenwen; Wu, Wanlong; Sun, Fangfang; Gu, Liyang; Chen, Jie; Li, Jiajie; Li, Ting; Wang, Xiaodong; Ye, Shuang (Frontiers in Immunology, 2021)
Objectives The aim of this study was to investigate anti-synthetase syndrome (ASyS) patients who presented with recurrent episodes of fever and systemic inflammation. Methods A retrospective cohort of Chinese ASyS patients (n=126) in our center (between January 2013 and January 2020) was included. Patients presenting with concomitant autoimmune rheumatic diseases or malignancies were subsequently excluded. The number of non-infectious fever attacks and attack frequency were recorded and calculated. Patients with two or more attacks and within the upper three quartiles of attack frequency were defined as high-inflammation group. Univariate and multivariate analyses were carried out to characterize the high-inflammation subtype. Results Out of 113 eligible patients with an average of 5 years follow up, 25 patients were defined as the high-inflammation group (16 for anti-Jo1, 9 for anti-PL7), with an average of 1.12 attack/patient-year. Compared to low-inflammation group (0–1 attack only and a frequency lower than 0.5 attack/patient-year), the high-inflammation group had higher occurrence of fever and rapid progressive interstitial lung disease (RPILD) as the first presentation (84% vs. 21% and 40% vs. 9%, respectively, both p<0.01). Anti-PL-7 was related to the more inflammatory phenotype (p=0.014). Cumulative disease-modifying agent exposures (>=3) were much higher in the high-inflammation group (60% vs. 26%), while biological agents, i.e., rituximab and tocilizumab, showed better “drug survival” for Jo-1+ and PL-7+ ASyS patients with high inflammation, respectively, in our cohort. Conclusions ASyS with recurrent systemic inflammatory episodes reflects a subtype of more aggressive and refractory disease in the spectrum of ASyS. Increased awareness of this subtype might lead to more appropriate management.